Victims of a white man's war : blacks in concentration camps during the South African War (1899-1902) (Historia, 2021)
Traditionally the South African War was depicted in the historiography as almost exclusively a white man's war. Prior to 1980 books contained very little information on black participation in the war and blacks were perceived as being mere spectators during the war. In the last twenty years historians have increasingly given attention to the participation by blacks in the South African War. These historians have proved that blacks were active participants who played a significant role in the war. It is a well-known fact that a concentration camp system was introduced in 1900 as part of the British military strategy to end Boer resistance during the guerrilla phase of the South African War. Boer women and children were removed from the land and brought into concentration camps. By the end of the war there were more than 40 camps for whites with a population of over 116 000.
Keywords: guerrilla phase of the South African War; Boer women and children; British military strategy; white man's war; concentration camp system; participation by blacks; Blacks